The "bush doctrine" and preemptive strike - a new approach in the right of self-defense? - Fiebich, Kristina Claudia (Centre for Law and Society, 2026)
Throughout the history of international law, there have always been acts of aggression, wars, and threats carried out by one state against another, directed against the territory or sovereignty of states, or against other protected interests. Even though there have been several attempts to restrict the use of force between states, neither the early doctrines of "just war" (justum bellum) of Grotius and Thomas Aquinas,1 nor subsequent multilateral treaties - the Covenant of the League of Nations of 1919, the "Kellog Briand-Pact" of 1928,2 and ultimately the Charter of the United Nations (U.N. Charter) of 19453 - have been able to eliminate entirely the use of force from the international stage.